2022
DOI: 10.3390/nano12060970
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Superstructure Arrays Fabricated by Laser Near-Field Reduction for Wide-Range SERS Analysis of Fluorescent Materials

Abstract: Surface-enhanced Raman scattering (SERS) enables trace-detection for biosensing and environmental monitoring. Optimized enhancement of SERS can be achieved when the energy of the localized surface plasmon resonance (LSPR) is close to the energy of the Raman excitation wavelength. The LSPR can be tuned using a plasmonic superstructure array with controlled periods. In this paper, we develop a new technique based on laser near-field reduction to fabricate a superstructure array, which provides distinct features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The silver nuclei induced LSPR to enhance the surface electric field and subsequently attracted the silver ions, leading to a continuous reduction process to form silver nanoparticles. [ 22 ] In addition, the synthesized silver nanoparticles were capped by citrate, indicating the presence of a strongly negatively charged surface (zeta‐potential: −39.66 mW). The negative charges were accumulated at the silver nanoparticle surface to facilitate the growth of silver nanoparticles.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…The silver nuclei induced LSPR to enhance the surface electric field and subsequently attracted the silver ions, leading to a continuous reduction process to form silver nanoparticles. [ 22 ] In addition, the synthesized silver nanoparticles were capped by citrate, indicating the presence of a strongly negatively charged surface (zeta‐potential: −39.66 mW). The negative charges were accumulated at the silver nanoparticle surface to facilitate the growth of silver nanoparticles.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Several applications of laser-structured surfaces have been already addressed in relation to their intriguing optical, wetting, mechanical, and biological-active properties [ 1 , 2 , 3 , 4 , 5 ]. However, they might express their potential in other fields like, for example, those pursuing the elaboration of nano-engineered plasmonic surfaces for SERS and metal-enhanced fluorescence [ 30 , 31 , 32 , 43 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Only few studies on the detection of PFAS using SERS have been reported today although there is an urgent need to develop rapid and ultrasensitive detection methods (M.B et al, 2023). In 2022, Bai et al created plasmonic superstructure arrays made of Ag nanoparticles and used them to detect PFOA during SERS analysis (Bai et al, 2022). To prevent luorescence and promote Raman signal detection, the authors incorporate crystal violet into PFOA.…”
Section: Surface-enhanced Raman Spectroscopy (Sers)mentioning
confidence: 99%